Analysis of 2017 Gartner’s Three Megatrends to Thrive the Disruptive Business, Technology Trends 2008-2016, Dynamic Capabilities of VUCA and Foresight Leadership Tools - Jari, Kaivo-Oja; Lauraeus, Theresa (Advances in Technology Innovation, 2019)
Nowadays, digitalization is the key element of business competition. This paper analyzes the concept of dynamic capabilities in the context of technological and business digitalization. We investigate the dynamic competence needed to create and manage a new Digital business, which is emerging from the technological transformation. Firstly, in this paper, we analyze the data of Gartner Hype Cycles 2008-2017. Thus, we present a comparative analysis of the changes in the Gartner hype cycle. Secondly, our aim is to present Gartner´s three distinct megatrends. We will present a summary of these Gartner evaluations and discuss key tendencies and trends of technological changes. Thirdly, the special focus of this article is the challenges of orchestration of dynamic capabilities in the special conditions of VUCA business disruptive business competition. Further, we define the role of competence gap identification inside a firm. Finally, we are presenting some useful tools to manage dynamic capabilities.